The Kunitz Domain I of Hepatocyte Growth Factor Activator Inhibitor-2 Inhibits Matriptase Activity and Invasive Ability of Human Prostate Cancer Cells. Issue 1 (December 2017) - Wu, Shang-Ru; Teng, Chen-Hsin; Tu, Ya-Ting; Ko, Chun-Jung; Cheng, Tai-Shan; Lan, Shao-Wei; Lin, Hsin-Ying; Lin, Hsin-Hsien; Tu, Hsin-Fang; Hsiao, Pei-Wen; Huang, Hsiang-Po; Chen, Chung-Hsin; et al.
Abstract Dysregulation of pericellular proteolysis is often required for tumor invasion and cancer progression. It has been shown that down-regulation of hepatocyte growth factor activator inhibitor-2 (HAI-2) results in activation of matriptase (a membrane-anchored serine protease), human prostate cancer cell motility and tumor growth. In this study, we further characterized if HAI-2 was a cognate inhibitor for matriptase and identified which Kunitz domain of HAI-2 was required for inhibiting matriptase and human prostate cancer cell motility. Our results show that HAI-2 overexpression suppressed matriptase-induced prostate cancer cell motility. We demonstrate that HAI-2 interacts with matriptase on cell surface and inhibits matriptase proteolytic activity. Moreover, cellular HAI-2 harnesses its Kunitz domain 1 (KD1) to inhibit matriptase activation and prostate cancer cell motility although recombinant KD1 and KD2 of HAI-2 both show an inhibitory activity and interaction with matriptase protease domain. The results together indicate that HAI-2 is a cognate inhibitor of matriptase, and KD1 of HAI-2 plays a major role in the inhibition of cellular matritptase activation as well as human prostate cancer invasion.